Study of endothelial dysfunction and asymmetric dimethylarginine levels - Ya. V. Sirman; I. V. Savytskyi (Kazimierz Wielki University, 2019)
The aim of the study was to analyze changes in the level of endothelin-1 and asymmetric dimethylarginine in the development of endothelial dysfunction in experimental diabetic retinopathy and various methods of its correction. The study was performed on white Wistar rats weighing 180-200 g. According to the tasks of the animal were divided into 7 groups: As a result of our study proved a violation of the structural and functional state of the endothelium in experimental diabetic retinopathy, as evidenced by elevated levels of ADMA and endothelin-1 in 2nd group (p <0.001), most pronounced in the 3rd stage. It was confirmed that the correction of the studied complication of diabetes mellitus only with a hypoglycemic drug, even with long-term administration, does not correct the development of endothelial dysfunction (p <0.001). It was found that the addition of aflibercept and a solution of L-arginine in the correction to hypoglycemic drugs significantly (p <0.001) improves the condition of the endothelium, but does not solve the problem completely. It is observed that the correction of the simulated pathological condition by reducing hyperglycemia, administration of aflibercept and bromfenac (group № 5) has a positive effect on the normalization of endothelial function markers (p <0.001), but the effect is less pronounced than in the following groups. It was found that in rats in which diabetic retinopathy was simulated with subsequent correction of hyperglycemia, administration of aflibercept, L-carnitine and bromfenac (group № 6), the reduction of pathologically elevated levels of markers of endothelial dysfunction is more pronounced compared to the 3rd group, which indicates the feasibility of this method of correction. It was found that the most effective method of correction was in the 7th group of the experiment in which hyperglycemia was corrected, aflibercept, L-arginine and citicoline were obtained to normalize the levels of endothelial dysfunction markers - endothelin 1 and asymmetric dimethylarginine.